Alteration of organic macerals by uranium irradiation in lower Paleozoic marine shales - Zheng, Xiaowei; Schovsbo, Niels Hemmingsen; Bian, Leibo; Luo, Qingyong; Zhong, Ningning; Rudra, Arka; Goodarzi, Fariborz; Sanei, Hamed (International journal of coal geology, 2021)
Measuring the degree of organic matter (OM) alteration caused by uranium (U) irradiation is important in the effective evaluation of the hydrocarbon potential and thermal maturity of U-rich source rocks. This study investigates OM alteration in the Baltoscandian U-rich, lower Paleozoic Alum shale obtained from three research wells in the thermally immature parts of eastern Sweden and western Estonia. The results show a marked increase in the proportion of refractory, non-generative organic carbon (NGOC) in the U-rich shale. Fluorescence spectrometry of unicellular alginites and lamalginites show a reduction of up to 95.6% in fluorescence relative intensity (RI) with increase in U content from 29 to 401 ppm. Fluorescence spectra of the liptinites exhibit a marked “red shift” as expressed by increase in red(R)/green(G) quotients. This change in fluorescence properties of the liptinites is associated with up to 77.6% decrease in hydrogen index (HI) and hence loss of hydrocarbon generation potential. Furthermore, organic molecules show significant loss of aromatic moieties as well as aliphatic constituents resulting in a more condensed macromolecular structure. The measured random reflectance of solid bitumen (BRo) appears to be significantly elevated in micro scale proximity to the U-containing minerals. The heterogeneous distribution of U-containing minerals and the contact with solid bitumen attributes to the wider range of BRo values and lead to the overall increase in mean BRo in samples with high U contents. In contrast, Ro values of zooclast macerals (GRo, e.g., graptolite, chitinozoans and vitrinite-like fragments) appear to be less influenced by U irradiation and hence are a more reliable maturity indicator in U- rich lower Paleozoic shales. •Uranium (U) irradiation is responsible for alteration of organic matter, manifested by red shift in fluorescence spectra of liptinites (Red/Green quotient) and increase in solid bitumen (thucholite) reflectance (BRo).•U irradiation attribute to hydrogen index (HI) decrease, relative non-generative organic carbon (NGOC) increase and parent macromolecule condensation.•Zooclast fragments (GRo, Graptolite, Chitinzoan and vitrinite-like particles) are more reliable maturity indicators in U-rich rocks.